Carbon‐Based Metal‐Free Catalysts for Key Reactions Involved in Energy Conversion and Storage - Zhao, Shenlong; Wang, Da‐Wei; Amal, Rose; Dai, Liming (Advanced materials (Weinheim), 2019)
Electrocatalysts are key for renewable energy technologies and other important industrial processes. Currently, noble metals and metal oxides are the most widely used catalysts for electrocatalysis. However, metal‐based catalysts often suffer from multiple disadvantages, including high cost, low selectivity, poor durability, impurity poisoning and fuel crossover effects, and detrimental effects on the environment. Therefore, carbon‐based metal‐free catalysts have received increasing interest as promising electrocatalysts for advanced energy conversion and storage. Recently, tremendous progress has been achieved in the development of low‐cost, efficient carbon‐based metal‐free catalysts for renewable energy technologies and beyond. Here, a concise, but comprehensive and critical, review of recent advances in the field of carbon‐based metal‐free catalysts is provided. A brief overview of various reactions involved in renewable energy conversion and storage, including the oxygen reduction reaction, hydrogen evolution reaction, oxygen evolution reaction, carbon dioxide reduction reaction, nitrogen reduction reaction, and bifunctional/multifunctional electrocatalysis, along with some challenges and opportunities, is presented. The emerging carbon‐based metal‐free catalysts have been demonstrated to be promising alternatives to noble metal/metal oxide catalysts for various reactions, including the oxygen reduction reaction, the hydrogen evolution reaction, the oxygen evolution reaction, the carbon dioxide reduction reaction, and the nitrogen reduction reaction, and for bi/multifunctional electrocatalysis. A concise, but comprehensive and critical overview of this field, including preparation strategies, mechanisms, and applications, along with some challenges and perspectives, is presented.